Analysis of Nutrient and Fatty Acid Composition of Different By-products of Yellowfin Tuna in South China Sea - Yaogang WU; Yuke HE; Zhou ZHAO; Hui YU; Zhiqiang GUO; Juan XIAO (Shipin gongye ke-ji, 2024)
In order to investigate the differences in weight proportion and nutrient composition of different by-products of yellowfin tuna, this study investigated the differences in the ratio of the by-products weight to the body weight of yellowfin tuna in different sizes. The differences in the content of moisture, protein, fat, ash and the profile of fatty acids were also analyzed. The results showed that the ratio of dark meat, head, and viscera weight to body weight ranged from 5.85% to 6.81%, from 10.62% to 21.05%, and from 4.20% to 7.47%, respectively. There was a significant difference in the moisture content of the different by-products (P<0.05), in which the pancreas had the lowest moisture content (65.37%) while the heart had the highest moisture content (72.93%). The protein and fat content varied significantly among the by-products (P<0.05). Protein content accounted for 49.25%~88.42% in dry body weight and 16.92%~29.24% in wet body weight, whereas fat content accounted for 2.98%~30.43% in dry body weight and 0.98%~10.46% in wet body weight. The head had the lowest protein content and the highest fat content among the by-products. Ash content of the head was 17.44% in wet body weight and 5.99% in dry body weight, and ash content of other by-products accounted for 4.10%~8.25% in dry body weight and 1.21%~2.43% in wet body weight. Twenty-six fatty acids were identified in all seven by-products. Palmitic, stearic, oleic, eicosapentaenoic, and docosahexaenoic acids were the predominant fatty acids. And their contents were significantly different among the by-products (P<0.05). In by-products except for the spleen, the unsaturated fatty acids accounted for more than 50.00% of the total fatty acids content, with which the highest was 66.07%. In summary, the weight of by-products in yellowfin tuna accounts for 21.63% to 34.36% of the body weight of the fish, which had an abundance of nutrients, and would used for the preparation of functional components such as flavor amino acids, antioxidant peptides and collagens.